Exosomes, metastases, and the miracle of cancer stem cell markers - Wang, Zhe; Zöller, Margot (Cancer and metastasis reviews, 2019)
Cancer-initiating cells (CIC) are the driving force in tumor progression. There is strong evidence that CIC fulfill this task via exosomes (TEX), which modulate and reprogram stroma, nontransformed cells, and non-CIC. Characterization of CIC, besides others, builds on expression of CIC markers, many of which are known as metastasis-associated molecules. We here discuss that the linkage between CIC/CIC-TEX and metastasis-associated molecules is not fortuitously, but relies on the contribution of these markers to TEX biogenesis including loading and TEX target interactions. In addition, CIC markers contribute to TEX binding- and uptake-promoted activation of signaling cascades, transcription initiation, and translational control. Our point of view will be outlined for pancreas and colon CIC highly expressing CD44v6, Tspan8, EPCAM, claudin7, and LGR5, which distinctly but coordinately contribute to tumor progression. Despite overwhelming progress in unraveling the metastatic cascade and the multiple tasks taken over by CIC-TEX, there remains a considerable gap in linking CIC biomarkers, TEX, and TEX-initiated target modulation with metastasis. We will try to outline possible bridges, which could allow depicting pathways for new and expectedly powerful therapeutic interference with tumor progression.